Retrospective Evaluation of Risk Factors and Outcome in Dogs With and Without Fluid Overload During Hospitalization - Alexandra Pfaff; Emmanuelle M. Butty; Elizabeth A. Rozanski; Armelle M. deLaforcade; Jacqueline N. Hicks; Noa Berlin (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Risk factors for the development of fluid overload (FO) and its potential negative effects have not been investigated in dogs. Hypothesis/Objectives Evaluate risk factors and outcomes in hospitalized dogs that received fluids IV and developed clinical signs of FO compared to those that did not. Animals One hundred thirty‐six dogs that developed FO and 109 dogs without FO. Methods Retrospective observational study of hospitalized dogs. Variables were compared between dogs that developed clinical signs of FO (FO group) and dogs without FO (control group). Results Compared to the control group, dogs in the FO group were significantly more likely to have cardiovascular disease (odds ratio [OR], 18.1; 95% confidence interval [CI], 5.4–60), protein‐losing nephropathy (OR, 15.3; 95% CI, 2.0–116.8), chronic kidney disease (OR, 10; 95% CI, 3.0–33.8), and acute kidney injury (OR, 5.2; 95% CI, 2.5–10.6). The total fluid volume administered IV was not significantly different between the groups (p = 0.16). Only 6.0% of dogs with clinical signs of FO gained > 10% weight from non‐dehydrated baseline and thus met the FO definition used in human medicine. Compared with the control group, dogs with FO had a significantly longer median duration of hospitalization (p < 0.001) and were less likely to survive to discharge (p < 0.001). Conclusions and Clinical Importance FO was more common with certain underlying diseases but not associated with total fluid volume administered IV. The definition for FO in human medicine using weight gain requires further evaluation in dogs. FO was associated with worse outcomes and longer hospitalization time.